Relationships Between Cognitive Distortions And Psychological Resilience On Cyber Delinquent Behaviour Among Saudi Arabia Adolescent - Alenezi, Fahad Neda (2022)
This study was conducted to examine the influence of cognitive distortions and psychological resilience on cyber delinquent behaviour among adolescents in Saudi Arabia. This study also aimed to examine the moderation effect of gender between all relationships. Employing a mixed-method design, a survey study of 386 students was first conducted and data were interpreted based on structural equation modeling (SEM). Then, eight key informants were interviewed and data were analyzed using deductive and inductive approaches. Two key findings emerged from the analyses. First, blame others, self-centered, and assuming the worst was significantly positively influenced cyber delinquent behavior were significantly positive influenced cyber delinquent behavior. The results also showed that optimism, hardiness, resourcefulness were significantly negatively influenced cyber delinquent behavior. Second, gender moderated the relationship between resourcefulness and cyber delinquent behaviour such relationship was stronger for female adolescents than for males. This research contributes to the understanding of how gender differences lead to cyber delinquent behavior by demonstrating that females are dominant in the association between resourcefulness and cyber delinquent behavior. Upon theoretical implications, this study also offered several policies and practical implications.